STUDY OF THE PROCESS OF DECOMPOSITION OF DOLOMITE "SHORSU" WITH NITRIC ACID TO OBTAIN A SOLUTION OF CALCIUM AND MAGNESIUM NITRATES (Western European Journal of Modern Experiments and Scientific Methods, 2025)
This article examines the possibility of obtaining a solution of calcium and magnesium nitrates by decomposing dolomite m.r. "Shorsu" with nitric acid. The process of decomposition of dolomite with nitric acid was studied depending on the concentration of the acid and temperature.